Early morning urine collection to improve the sensitivity of LAM in hospitalised TB/HIV co-infected patients - Gina, Ntombenhle Phindile (Division of Pulmonology, 2016)
Point-of-care detection of urine lipoarabinomannan (LAM) is a low-cost rapid TB diagnostic for use in HIV co-infected patients. However, its sensitivity in these patients is suboptimal. Strategies to improve its performance is a need. The hypothesis was that early morning urine (EMU), rather than random urine sampling, would improve LAM's sensitivity. Methods Recruitment process conducted between June 2012 and February 2014 for HIV-infected patients from four hospitals in Cape Town, South Africa presenting with possible TB (all patients initiated on TB treatment). Fresh random and early morning urine (EMU) samples (~10-30 ml) collected in sterile containers. Following the manufacturer's instructions, an Alere Determine® TB Lateral flow assay performed on each sample, using both grade 1 and 2 cut-points. A single sputum Xpert MTB/RIF and/or liquid TB culture was a reference standard. Those designated probable TB patients were sputum Xpert MTB/RIF and/ TB culture negative, but started on TB treatment.